GLOMERULOPATIA EM UM HOSPITAL UNIVERSITÁRIO: ANÁLISE ANATOMOPATOLÓGICA COM 409 BIÓPSIAS EM RINS NATIVOS - Alves, Janeide Leonar Carvalho (2012)
Introduction: Prevalence of glomerulopathies in a Teaching Hospital. Epidemiologic data on renal diseases based on populations are limited. A better view around the clinically significant glomerulonephritis can be acquired from diagnosis by renal biopsy. Objectives: To determine the prevalence of glomerulopathies, classify them according to the classification of the World Health Organization. Methods: Transversal descriptive study, based on medical records of biopsied patients as well as on their histopathological technical opinions of 409 renal biopsies, executed between january of 1999 and december of 2010 in Presidente Dutra School Medicine Hospital s Nephrology Service of the Universidade Federal do Maranhão (UFMA) Results: The most common glomerulopathy, both in adults and in patients under 20 years old, was segmental glomerulosclerosis and focal glomerulosclerosis (22%) and nephrotic syndrome was found as the most common glomerular syndrome at the moment of diagnosis, in patients of all ages. Most of the diagnoses occurred in patients between ages of 20 to 39 years old, corresponding to 42,05% of all biopsies, a number that decreases as patients are nearer to the extremities of life. There was a balance between sex distributions, but with a remarkable predominance of the female sex in lupus nephritis (88,60 %). Conclusion: The epidemiologic profile of glomerulopathies in a School Hospital in Maranhão resembled the ones found in national level. These data supply important bases to future studies on glomerulopathies in Maranhão.